Pengaruh Pengambilan Keputusan, Dukungan Suami dan Faktor Budaya Terhadap Lamanya Proses Persalinan di Kabupaten Timor Tengah Selatan Tahun 2019 - Mareta Bakale Bakoil; Martina Fenansia Diaz (FORIKES, 2020)
South Central Timor Regency is one district with a high maternal mortality rate compared to 21 other districts. One of the socio-cultural factors in South Central Timor Regency is the husband as a decision maker in the family including in the search for services and place of delivery. The purpose of this study was to determine the relationship between decision making, husband support, and cultural factors on the length of labor. This type of research was analytic observational with cross sectional design. The population was all maternity mothers. The sample size was 100 people using accidental sampling technique. The independent variables were decision making, husband's support, and cultural factors. The dependent variable was the length of labor. Data collection used a questionnaire to measure decision-making variables, cultural factors, and the length of labor, while the husband's support variables was observed using a check list. Data were analyzed descriptively and inferentially using the SPSS statistical program. The results showed that more mothers were included in healthy reproductive age with low parity, the majority of mothers with high education, decision making tended to be quite good category, the majority of husbands supported mothers in labor, the duration of labor